Combinational Effect of Cell Adhesion Biomolecules and Their Immobilized Polymer Property to Enhance Cell-Selective Adhesion - Rio Kurimoto (International Journal of Polymer Science, 2016)
Although surface immobilization of medical devices with bioactive molecules is one of the most widely used strategies to improve biocompatibility, the physicochemical properties of the biomaterials significantly impact the activity of the immobilized molecules. Herein we investigate the combinational effects of cell-selective biomolecules and the hydrophobicity/hydrophilicity of the polymeric substrate on selective adhesion of endothelial cells (ECs), fibroblasts (FBs), and smooth muscle cells (SMCs). To control the polymeric substrate, biomolecules are immobilized on thermoresponsive poly(N-isopropylacrylamide-co-2-carboxyisopropylacrylamide) (poly(NIPAAm-co-CIPAAm))-grafted glass surfaces. By switching the molecular conformation of the biomolecule-immobilized polymers, the cell-selective adhesion performances are evaluated. In case of RGDS (Arg-Gly-Asp-Ser) peptide-immobilized surfaces, all cell types adhere well regardless of the surface hydrophobicity. On the other hand, a tri-Arg-immobilized surface exhibits FB-selectivity when the surface is hydrophilic. Additionally, a tri-Ile-immobilized surface exhibits EC-selective cell adhesion when the surface is hydrophobic. We believe that the proposed concept, which is used to investigate the biomolecule-immobilized surface combination, is important to produce new biomaterials, which are highly demanded for medical implants and tissue engineering.